Petrology and geochemistry of the Langkawi granites / Kyaw Kyaw Nyein - Kyaw, Kyaw Nyein (2014)
The Langkawi Islands comprises a group of 99 tropical islands lying off the northwest coast of Peninsular Malaysia. The Langkawi granite makes about 40 % of the Langkawi. It can be divided into two main bodies: Gunung Raya and Kuah granites. The Gunung Raya biotite granite shows very coarse- to medium-grained texture, some are strongly porphyritic with K-feldspar phenocrysts reaching 6 cm in length whereas the Kuah granite consists of highly evolved fine- to medium-grained tourmaline granite. Tourmaline occurs in both Gunung Raya and Kuah granite. The tourmalinization is clearly observed in the Kuah granite. Geochemically, the Kuah granite (75.1-77 %SiO2) has more siliceous and evolved magma than the Gunung Raya granite (68.1-75.3 %SiO2). The highly evolved magma for the Kuah granites is also supported by high Rb/Sr ratio (~20.55), compared to the Gunung Raya granite which is much less it is differentiated (~7.84). The distinct negative anomalies for Nb, Sr, and Ti are showing typical upper crustal compositions. In addition, the negative anomalies in Ba, Nb, Sr, and Ti that become increasingly marked towards the most felsic and fractionated granitic facies: such trends are typical of collisional peraluminous granitoids. All granites have ASI >1 which is peraluminous. Both the Gunung Raya and Kuah granite show fundamental S-type feature like peraluminous composition, high K2 O / Na2 O ratio (~1.56 %), low total Fe and restricted composition range dominated by high SiO2, normative corundum > 1%. Strongly negative Eu anomaly is normally subscribed to fractionation of plagioclase due to the similar ionic radius and charge of Eu2+ and Ca2+. The rare earth element (REE) pattern of the Langkawi granite constitutes familiar birds-wing REE pattern and strong negative Eu anomaly which is similar to the dominant S-Type granites of the Main Range. Major and trace elements Harker diagram and large ion lithophile (LIL) modeling suggest that the Gunung Raya and Kuah magmas were derived from the different magmatic pulses. Both pluton are controlled by the same mineral assemblages (plagioclase + K-feldspar and biotite) suggest that they may be formed from the same magmatic source. The Langkawi granite has K - Ar and Rb - Sr dates (217 ± 8 Ma and 209 ± 6 respectively). The Late Triassic age suggested that the granites may falls within the syn-collisional granites. The S-type characteristic associated with the tin mineralization clearly indicates that it is related to the Indosinian Orogeny.